South African Jazz in Frame: A creative research project exploring South African jazz through photography - Hendricks, Lauren (College of Music, 2024)
The aim of this creative research project was to investigate and document the closely connected relationships between South African jazz musicians and South African jazz photographers through their contributions such as the images, videos and the stories behind each of the respective art forms. The research looks at the specific contributions selected photographers have made to the South African jazz genre, in documenting the process and the art. The intent was to explore the creative process of seeing South African jazz documented in imagery, and through sound and music. This project also sought to unpack the artistic and creative approaches used by the selected photographers, and investigated their relationship with the music. The project explores the idea of telling stories through both respective art forms, through image and sound, and reflecting this through a curated performance and exhibition. Qualitative research methods were used to inform the creative process. The research process was conducted in two parts: semi-structured interviews with three selected South African jazz photographers, followed by a concert performance combined with an exhibition of selected photographs by the three jazz photographers, and some of my own work. By uniting a visual exhibition and a live performance presenting South African jazz music, I aimed to create an intimate and captivating experience. Through the live performance, the project aimed to explore how sound and image relate, Furthermore, this project has shed light on the complexities of capturing live jazz performances, and how the photographs have documented and celebrated the richness and diversity of South African jazz.